2013
DOI: 10.1038/srep01055
|View full text |Cite
|
Sign up to set email alerts
|

The VMP1-Beclin 1 interaction regulates autophagy induction

Abstract: The Vacuole Membrane Protein 1 -VMP1- is a pancreatitis-associated transmembrane protein whose expression triggers autophagy in several human diseases. In the current study, we unveil the mechanism through which this protein induces autophagosome formation in mammalian cells. We show that VMP1 autophagy-related function requires its 20-aminoacid C-terminus hydrophilic domain (VMP1-AtgD). This is achieved through its direct binding to the BH3 motif of Beclin 1 leading to the formation of a complex with the Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 44 publications
6
125
0
1
Order By: Relevance
“…The synchronized recruitment of ATG5 with ULK1 might be mediated by a recently described interaction between the ULK complex subunit FIP200 and ATG16L1 (Gammoh et al, 2013;Nishimura et al, 2013). The VMP1-beclin 1 interaction was also found to facilitate the association of ATG16L1 and LC3 (also known as microtubule-associated protein 1 light chain 3) with the autophagosomal membranes (Molejon et al, 2013). As VMP1 expression is known to trigger autophagy (Ropolo et al, 2007) and because it seems to be the most 'temporally' upstream factor identified to date, it is tempting to hypothesize that VMP1 acts as a recruitment platform that determines the site of phagophore formation by recruitment of the early core ATG proteins.…”
Section: Phagophore Nucleationmentioning
confidence: 94%
See 1 more Smart Citation
“…The synchronized recruitment of ATG5 with ULK1 might be mediated by a recently described interaction between the ULK complex subunit FIP200 and ATG16L1 (Gammoh et al, 2013;Nishimura et al, 2013). The VMP1-beclin 1 interaction was also found to facilitate the association of ATG16L1 and LC3 (also known as microtubule-associated protein 1 light chain 3) with the autophagosomal membranes (Molejon et al, 2013). As VMP1 expression is known to trigger autophagy (Ropolo et al, 2007) and because it seems to be the most 'temporally' upstream factor identified to date, it is tempting to hypothesize that VMP1 acts as a recruitment platform that determines the site of phagophore formation by recruitment of the early core ATG proteins.…”
Section: Phagophore Nucleationmentioning
confidence: 94%
“…ATG14L contains an ER-binding motif in its N-terminal domain, which appears to be essential for its function in autophagy and for the recruitment of the other PI3KC3 subunits (see Box 1) to the sites of phagophore formation ). An interaction between VMP1 and beclin 1 (Molejon et al, 2013) might further stabilize the association of the PI3KC3 complex with the ER membrane. Finally, the ATG12-ATG5-ATG16L1 complex (see Box 1) is recruited to the phagophore ( Fig.…”
Section: Phagophore Nucleationmentioning
confidence: 99%
“…Perhaps more importantly, the expression of vacuole membrane protein 1 (VMP1) is increased in AP and mediates "zymophagy," a selectively autophagic pathway to remove zymogen granules, and prevents pancreatic acinar cell death by interaction with Beclin1, an essential regulator of autophagy and apoptosis (71)(72)(73)(74). Mitochondrial injury and lipid abnormalities have been associated with pancreatitis (66).…”
Section: Autophagymentioning
confidence: 99%
“…A great number of studies have previously demonstrated that the Beclin-1-Vps34-Vps15 multimeric complex can govern the nucleation of autophagy, as evidenced by the increased interaction between Beclin-1 and the Vps34-Vps15 complex in response to either starvation or rapamycin treatments (19,35,36). Given that Beclin-1 has been shown to interact physically with ErbB2 (37), we thus reasoned that ErbB2 could bind to Beclin-1 and modulate the autophagic flux to control the autophagic clearance of C99 and AICD.…”
Section: An Shrna Screen Identified Candidate Genes That Differentiallymentioning
confidence: 99%